2015
DOI: 10.1002/ece3.1489
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ecological traps for the control of feral pigs

Abstract: Ecological traps are habitat sinks that are preferred by dispersing animals but have higher mortality or reduced fecundity compared to source habitats. Theory suggests that if mortality rates are sufficiently high, then ecological traps can result in extinction. An ecological trap may be created when pest animals are controlled in one area, but not in another area of equal habitat quality, and when there is density-dependent immigration from the high-density uncontrolled area to the low-density controlled area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(103 reference statements)
2
4
0
Order By: Relevance
“…When we scaled our deterministic models to have the same intrinsic population growth rates as our stochastic model, we found that the general patterns were similar between the two approaches but that the stochastic model tended to have larger abundances for slightly longer, and tended to persist longer. Thus, our results support Dexter & McLoed [ 55 ] because we found that the birth-pulse fluctuations in our stochastic model led to different effects of culling patterns on abundance trajectories relative to our deterministic models. But, in contrast to [ 55 ], we found that the populations with stochasticity tended to be more robust at low abundance because of the potential for higher fecundity at low densities relative to the deterministic models.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When we scaled our deterministic models to have the same intrinsic population growth rates as our stochastic model, we found that the general patterns were similar between the two approaches but that the stochastic model tended to have larger abundances for slightly longer, and tended to persist longer. Thus, our results support Dexter & McLoed [ 55 ] because we found that the birth-pulse fluctuations in our stochastic model led to different effects of culling patterns on abundance trajectories relative to our deterministic models. But, in contrast to [ 55 ], we found that the populations with stochasticity tended to be more robust at low abundance because of the potential for higher fecundity at low densities relative to the deterministic models.…”
Section: Discussionsupporting
confidence: 90%
“…Previous work suggests that the impacts of culling may be underestimated in deterministic models that neglect fluctuations around carrying capacity and lag times in reproductive processes [ 55 ]. When we scaled our deterministic models to have the same intrinsic population growth rates as our stochastic model, we found that the general patterns were similar between the two approaches but that the stochastic model tended to have larger abundances for slightly longer, and tended to persist longer.…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not undergo concentrated efforts to remove wild pigs during our baiting program in 2016, and had minimal removal in 2018, thus most animals remained on the landscape following baiting activities. Previous studies have suggested that wild pigs from surrounding areas will quickly immigrate into areas left vacant by control efforts (Bodenchuk, 2014;Dexter and McLeod, 2015). It is unclear how immigration would further influence movement behaviors of any remaining wild pigs following baiting programs, but could possibly exasperate the negative consequences such as spread of diseases.…”
Section: Tablementioning
confidence: 99%
“…They are most widespread in the tropical north, yet spatial knowledge is either empirical, detailed, and local scale [ 16 22 ], or expert-based, coarse, broad scale, and poorly validated [ 23 – 25 ]. Improved regional-scale knowledge of wild pig distribution could be used to delineate management units and limit re-invasion of conservation sites following local eradication [ 13 , 26 ]. It could also help assess the magnitude of environmental and economic impacts or the risk of establishment of infectious animal diseases, especially when abundance estimates are derived [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%